Kejaman in Malaysia: Decreasing language ability and uniplexity of social networks. - Amee, Joan; Ting, Su Hie (Asia-Pacific International University, Muak Lek, Thailand, 2022)
This study examined the influence of social networks on the language ability of Kejaman speakers, a small indigenous group in Sarawak, Malaysia. Using questionnaires, data were collected from 123 participants from three generations of Kejaman speakers who lived in two longhouses located in Belaga, Sarawak. The results showed good to excellent ability in Kejaman among the grandparents and parents’ generation, but fewer of the children’s generation were able to interact fluently and spontaneously in Kejaman. Based on frameworks for social network analysis, the Kejaman had a looseknit social network characterised by a low density and uniplex social network pattern, indicating dependence on a selected number of kin and non-kin contacts. The average number of contacts in their exchange and interactive network was three each for all three generations. The grandparents’ generation was close to having a multiplex social network (49.1%), but the other two generations had uniplex social networks of 21% to 25%. There were significant negative correlations between ability to speak Kejaman and the number of exchange and interactive networks. Their networks comprise contacts from other ethnic groups. Therefore, having more contacts and interactions with non-Kejaman speakers was associated with a lower level of Kejaman ability.